The reaction can be represented as following:
6NH4OH + Bi2(SO4)3 --> 2Bi(OH)3 + 3(NH4)2SO4
From the reaction:
m(NH4OH) / [6 × Mr(NH4OH)] = m(Bi(OH)3) / [2 × Mr(Bi(OH)3)] = m(Bi2(SO4)3) / Mr(Bi2(SO4)3)
From here:
m(NH4OH) = [m(Bi(OH)3) × 6 × Mr(NH4OH)] / [2 × Mr(Bi(OH)3)] = [16g × 6 × 35] / [2 × 260 g/mol] = 6.46 g
m(Bi2(SO4)3) = [m(Bi(OH)3) × Mr(Bi2(SO4)3)] / [2 × Mr(Bi(OH)3)] = [16 g × 706 g/mol] / [2 × 260 g/mol] = 21.72 g
Answer: 6.46 g of NH4OH and 21.72 g of Bi2(SO4)3.
Comments
Leave a comment